La prise en compte du numérique par les agences d’urbanisme : évaluation de la situation française - Philippe Vidal; Marie-Hélène Gauthier (Cybergeo, 2021)
This article examines the role of urban planning agencies in a metropolised urban environment where digital development is a new political objective. It repositioned the urban planning agencies among the various public and private engineering supports for metropolises and agglomerations committed to a "Smart City" strategy. The article shows that there is a wide range of levels of commitment by the agencies, from a desire to bring issues as close to the actors as possible to a certain avoidance of the subject, which is considered to be of low priority despite the growing commitment of partner authorities. A national ranking of investment over the 2010-2018 period is proposed here. The article deciphers the reasons for this differentiated level of consideration and puts forward some arguments for the future strengthening of agencies in this area.